EFEKTIFITAS EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) TERHADAP KUMBANG BERAS (Sitophylus oryzae L.) - Susanti1 Susanti1; Moh yunus2; Flora pasaru (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
Sitophilusoryzae L. is an important insectin warehouses causing damages to rice grainsand assisting fungal growthto spreadin a short time.  This leads to the rice grain become inconsumable. Symptoms of attacksinclude holes in rice grains or the rice grains change into flour. This study aimed to determine the effectiveness of extracts of fragrant pandan leaves (Pandanus amaryllifolius Roxb.) in controlling Sitophylusoryzae L.  The research was carried out in the Laboratory of Disease of TadulakoUniversity and arranged in a completely randomized design (CRD) with five treatments and replicated five times. The treatments included control (without treatment, A0), 5% fragrant pandan leaf extract (A1), 10% fragrant pandan leaf extract (A2), 15% fragrant pandan leaf extract (A3), and 20% fragrant pandan leaf extract (A4). Data was then analyzed using analysis of variance followed by a HSD test at 5% level when the treatments had significant effect. The study showed that the leaf extract of P. Amaryllifoliussignificantlyaffected the mortality ofSitophylusoryzae L observed at oneWAA (week after application), two WAA, and three WAA. The leaf extracts of P. amaryllifoliusapplied at theconcentration of 20% is more effective in controlling Sitophylusoryzae L atone WAA, two WAA, and three WAA. The insect mortality was 57.87% at the concentration of 20% while it was 50.52% at the concentration of 15%,30.16%at the concentration of 10%, 18.2% at the concentration of 5%, and least at Control.